Early, rapid and sensitive veterinary molecular diagnostics - real time PCR applications - Pestana, Erika; Belak, Sandor; Diallo, Adama; Crowther, John R.; Viljoen, Gerrit J.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
This book gives a comprehensive account of the practical aspects of Real time PCR and its application to veterinary diagnostic laboratories. The optimisation of assays to help diagnose livestock diseases is stressed and exemplified through assembling standard operating procedures from many laboratory sources. Theoretical aspects of PCR are dealt with as well as quality control features necessary to maintain an assured testing system. The book will be helpful to all scientists involved in diagnostic applications of molecular techniques, but is designed primarily to offer developing country scientists a collection of working methods in a single source. The book is an adjunct to the Molecular Diagnostic PCR Handbook published in 2005.
Background -- Traditional PCR -- Real-Time PCR #x2013; The Basic Principles -- New Trends in the Diagnosis and Molecular Epidemiology of Viral Diseases -- Disease Diagnosis Using Real-Time PCR Specific Procedures for Important Veterinary Pathogens -- PCR Laboratory Set-up -- Analysis and Troubleshooting -- Specifications for PCR Machines.
Keywords: Life sciences; Molecular biology; Virology; Infectious diseases; Agriculture; Biology -- Technique; Life Sciences; Biological Techniques; Infectious Diseases; Virology; Molecular Medicine; Agriculture; Biomedicine general; Electronic books